Concepciones y prácticas sobre la intervención psicosocial con agresores, desde la óptica de profesionales de la psicología que laboran en la ciudad de Quito. Producciones narrativas elaboradas entre noviembre del 2015 y marzo del 2016 - Moreira Carrasco, Andrea Carolina (2016)
Since the start intervention programs with violent men they recognized that this is a complex process that requires work on the transformation of unjust and degrading towards women relations, it is necessary to deepen the theme of violence from a feminist foundation. Currently two types of categories are evident to intervene with men who decide to exercise violence: intervention applies only technical procedures for controlling behavior and intervention that articulates a feminist conception for deep analysis of this complex problem. The feminist view argues that gender roles are socially constructed, this social construction reflects a patriarchal system that has subjectivized men and women to play inequitable roles, and it is for this reason that is necessary to deconstruct the imaginary and the limiting action of traditional roles. An essential concept to think of "aggressors" is masculinity, currently under discussion on men and masculinities dominant configuration. The patriarchal system has a model of masculinity that ranks the big man, which is characterized by the provider, is always willing to give pleasure, not afraid and solve their problems with aggression to show their strength, but express your feelings is a sign of weakness. For this reason it is necessary to question, discuss and reconstruct the meanings of masculinity, this process will not be easy but it is essential to understand the various changes in gender relations in public and private spaces.